2015
DOI: 10.1097/opx.0000000000000648
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Automated and Traditional Measures of Tear Film Breakup

Abstract: Purpose To determine repeatability and agreement between the non-invasive tear break up time (NIK-BUT) as measured by the Oculus Keratograph 4 and fluorescein tear break up time (FBUT). Methods Sixty subjects were recruited for two study visits separated by 7 (± 2) days. At each visit, three NIK-BUT measures and FBUT measures were obtained. Each NIK-BUT measure from the Keratograph included a first and an average NIK-BUT. The means of the measures obtained, first NIK-BUT, average NIK-BUT and FBUT, were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
3
34
0
1
Order By: Relevance
“…Acquiring a TBUT is a relatively simple task, but interpreting the result is not straightforward because of its inherent variability [80,81]. A number of approaches to improving repeatability have been suggested, including taking multiple readings and averaging or selecting a subset of values [82,83], minimizing the amount of fluorescein instilled [8486] and, most significantly, eliminating the use of fluorescein altogether.…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…Acquiring a TBUT is a relatively simple task, but interpreting the result is not straightforward because of its inherent variability [80,81]. A number of approaches to improving repeatability have been suggested, including taking multiple readings and averaging or selecting a subset of values [82,83], minimizing the amount of fluorescein instilled [8486] and, most significantly, eliminating the use of fluorescein altogether.…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…Oculus Keratograph can detect the very early changes of tear film and record very low NITBUT objectively with high reliability and repeatability [14,15]. Stephanie et al reported that NITBUT measured by Keratograph 4 can be substituted for the numerical fluorescein TBUT value [16]. The present study recorded the changes of both NITBUT-first and NITBUT-average after PPV via Keratograph 5M.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, these invasive examinations have been shown to have poor accuracy and reproducibility. The noninvasive Keratography 5M, advanced Placido topograph, provides reliable objective measurements of ocular surface parameters including tear meniscus height (TMH), noninvasive TBUT (NITBUT) and bulbar redness score, with acceptable repeatability and reproducibility [7,8]. It has been used in evaluation of ocular surface in recent years, especially the diagnosis of dry eye.…”
mentioning
confidence: 99%
“…Both NITBUT f and NITBUT avg are correlated with Ocular Surface Disease Index (OSDI) score 11. NITBUT f has better within-visit agreement with FTBUT than NITBUT avg 12 A 12.1 s NITBUT f has a 82% sensitivity and 94% specificity while a 5 s RBUT cut-off has a 82% sensitivity and 60% specificity in distinguishing DED from healthy subjects 10 13. These different platforms and algorithms have poor agreement among themselves and are not interchangeable 14.…”
Section: Imaging Techniquesmentioning
confidence: 99%